Analyzing Social Safety Net and Employment Assistance Spending in Chinese Cities (对中国城市中社会保障和就业援助支出的分析). Issue 3 (10th October 2013) - Ho, Alfred Tat‐Kei; Lang (堪萨斯大学，劳伦斯市，堪萨斯州), Tao
<x xml:space="preserve">Abstract</x> As social harmony and stability become increasingly important to the Chinese policymakers, how to use government spending to help the unemployed and needy population becomes a key task. Unlike many western countries, China pursues a highly decentralized policy in social safety net and employment assistance spending. This paper explores the advantages and challenges of this fiscal arrangement, and uses data of about 330 Chinese cities between 2007 and 2010 to analyze how this spending evolved during the ups and downs in the national economy. Based on various descriptive analyses and a hierarchical model, our results show that the Chinese government has indeed increased social safety net spending significantly over time. However, contrary to our prior expectation, cities with higher gross regional products per capita and cities in the richer coastal provinces spend less per non‐employed person, after controlling for the non‐employment population ratio in the cities. In general, the share of SSNEA budget in the total general budget has remained relatively stable despite economic ups and downs. From this perspective, China seems to be quite successful in maintaining a balanced approach to social assistance and has avoided the over‐expansion of welfare and pension spending that is being witnessed in many western countries.